NANOTECHNOLOGY PRINCIPLES OF OPTOELECTRONIC MODULE REALIZATION FOR RECORDING, PRESERVATION AND DISPLAY OF THE INFORMATION - Kozhemyako, Volodymyr P.; Yarovyy, Andriy A.; Novytsky, Ruslan M. (International Journal of Computing, 2014)
In given article use of the approaches, developed by the authors, is offered at designing separate structures of computing systems, which is based of optoelectronic principle of eye - processor information processing on the basis of dynamic multifunctionality, with the purpose of maintenance of development and application of nanotechnology optoelectronic high-performance elements and devices for their further integration in general structure of computing, laser and optoelectronic systems, and also systems of artificial intelligence.